Tea Flavonoids and Risk of Cardiovascular and All-Cause Mortality: A Systematic Review and Meta-Analysis (P06-126-19). (13th June 2019) - Wallace, Taylor; Cassidy, Aedin; Chung, Mei; Ferruzzi, Mario; Jacques, Paul; Johnson, Elizabeth; Wang, Ding Ding; Zhao, Naisi; Shams-White, Marissa; Karlsen, Micaela
Abstract: Objectives: To conduct a systematic review and meta-analysis evaluating the effects of tea flavonoids on cardiovascular (CVD) and all-cause mortality outcomes. Methods: Searches across five databases including PubMed and Embase were conducted through November 2018 to identify randomized controlled trials (RCTs) and prospective cohort studies reporting cardiovascular and all-cause mortality outcomes. Two investigators independently conducted abstract and full-text screenings, data extractions, and risk of bias (ROB) assessments using the Nutrition Evidence Library Bias Assessment Tool (NEL BAT). Mixed-effects dose-response meta-regression and standard random-effects meta-analyses for outcomes with ≥4 studies were performed. Results: 0 RCTs and 38 prospective cohort studies were included in the systematic review. NEL BAT scores ranged from 0–15 (0 being the lowest risk). Our linear meta-regression model showed that each cup increase in daily tea consumption (about 280 mg and 338 mg of total flavonoids for black and green tea, respectively) was associated with 3–4% lower risk of CVD mortality (predicted adjusted RR = 0.96; CI 0.93–0.99 for green tea and RR = 0.97; CI 0.94–0.99 for black tea). Furthermore, each cup increase in daily tea consumption was associated a 2% lower risk of all-cause mortality (predicted adjusted relative risk (RR) = 0.98; 95% CI 0.97–0.99 for black tea and RR = 0.98; CI 0.96–0.99 for green tea, respectively). Two studies reported multivariable Cox regression analysis results for the relationship between black tea intake and risks of all-cause mortality outcomes. The results from these two studies were combined with our linear meta-regression result in a random-effects model meta-analysis and showed that each cup increase in daily black tea consumption was associated with an average of 3% lower risk of all-cause mortality (pooled adjusted RR = 0.97; 95% CI 0.87–1.00) with large heterogeneity (I 2  = 81.4%; p = 0.005). Conclusions: Current evidence indicates that increased tea consumption may reduce CVD and all-cause mortality in a dose-response manner. This systematic review was registered on PROSPERO. Funding Sources: Funding for this study was provided through an unrestricted educational grant from Unilever. The funding body had no influence on the study design; the collection, analysis, and interpretation of data; the writing of the report; and the decision to submit the paper for publication.